Mathematical Model of One-dimensional Miscible Fluid Injection in Fractured Porous Media - JAMSHIDNEZHAD, M.; MONTAZER-RAHMATI, M. M.; SAJJADIAN, V. A. (Journal of the Japan Petroleum Institute, 2003)
A mathematical model for miscible displacement in fractured porous media is developed. The model takes into account advective, gravitational and crossflow mechanisms of mass exchange between fracture and matrix. The model is normalized by using the dimensionless parameters which characterize the process, and the analytical solutions of the resulting system of equations are provided by utilizing the method of characteristics. The model developed has been compared with experimental results and with previous model, which includes only crossflow between fracture and matrix. There is very good agreement between experiments and this model prediction.